Role of extracurricular activities in the development of leadership skills among the undergraduate Doctor of Physical Therapy students of Khyber Medical University and its affiliated institutes in Peshawar: A Cross-sectional study - Khan, Mahnoor Raza; Khan, Palwasha; Ali , Mehwish; Khan, Tajalla; Rahman, Mujeeb Ur; Ali Naqvi, Syed Muhammad Shabbir (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the role of extracurricular activities in the development of leadership skills among undergraduate Doctor of Physical Therapy students. Method: The cross-sectional study was conducted from March to October 2023 at the Khyber Medical University and its affiliated institutes in Peshawar, Pakistan, and comprised undergraduate Doctor of Physical Therapy students of either gender aged at least 18 years. Data was collected using a a pilot-tested questionnaire. Data was analysed using SPSS22. Results: Of the 340 students, 231(67.9%) were females and 109(32.1%) were males. The overall mean age was 21.55±1.75 years. The largest group was of students in the 7th semester 76(22.4%). Of the total, 131(38.5%) students were members of extracurricular societies, while 209(61.5%) were non-members. High-level leadership skills were found among the members compared to the non-members (p<0.001). Type of society (p<0.001) and gender (p=0.013) has a substantial association with leadership skills. Conclusion: The role of extracurricular activities in the development of leadership skills among undergraduate Doctor of Physical Therapy students was found to be significant. Key Words: Co-curricular activities, Extracurricular activities, Leadership skills, Leadership emergence, Skill development, Student leadership.